1999
DOI: 10.1101/gad.13.24.3185
|View full text |Cite
|
Sign up to set email alerts
|

T (Brachyury) is a direct target of Wnt3a during paraxial mesoderm specification

Abstract: Wnt3a encodes a signal that is expressed in the primitive streak of the gastrulating mouse embryo and is required for paraxial mesoderm development. In its absence cells adopt ectopic neural fates. Embryos lacking the T-boxcontaining transcription factors, Brachyury or Tbx6, also lack paraxial mesoderm. Here we show that Brachyury is specifically down-regulated in Wnt3a mutants in cells fated to form paraxial mesoderm. Transgenic analysis of the T promoter identifies T (Brachyury) as a direct transcriptional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
410
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(464 citation statements)
references
References 32 publications
(51 reference statements)
46
410
2
1
Order By: Relevance
“…ϩ and Ϫ indicate whether the cited references (shown in parentheses) reported expression by ISH, although, published results coming from Northern blots, RT-PCR or microarray studies are shown in brackets. Due to lack of space, not all references could be mentioned, however, the appropriate references as well as expression profiles can be found at the Gene Expression Database web page (2) Bouillet et al (1996); 10, Lloyd et al (2003);11, Zakin et al (2000); 12, Yamaguchi et al (1999);13, Takada et al (1994);14, Hoang et al (1998);15, Lescher et al (1998);16, Leyns et al (1997);17, Finley et al (2003); 18, Glinka et al (1998);19, Monaghan et al (1999).…”
Section: Multiple Specific Wnt Expression Patterns In the Blastocystmentioning
confidence: 99%
“…ϩ and Ϫ indicate whether the cited references (shown in parentheses) reported expression by ISH, although, published results coming from Northern blots, RT-PCR or microarray studies are shown in brackets. Due to lack of space, not all references could be mentioned, however, the appropriate references as well as expression profiles can be found at the Gene Expression Database web page (2) Bouillet et al (1996); 10, Lloyd et al (2003);11, Zakin et al (2000); 12, Yamaguchi et al (1999);13, Takada et al (1994);14, Hoang et al (1998);15, Lescher et al (1998);16, Leyns et al (1997);17, Finley et al (2003); 18, Glinka et al (1998);19, Monaghan et al (1999).…”
Section: Multiple Specific Wnt Expression Patterns In the Blastocystmentioning
confidence: 99%
“…However, in DVE-ablated embryos, Wnt3 was expressed in the proximal epiblast after culture (7/7). Thus, the DVE/AVE is required to maintain the posterior expression of Wnt3 and its downstream target T (Yamaguchi et al, 1999) (Fig. 2C',D').…”
Section: The Dve Is Required For Normal Positioning Of the Primitivementioning
confidence: 99%
“…A part of the Brachyury expression domain in the primitive streak depends on Wnt3a (Yamaguchi et al, 1999b) and the downstream effectors Lef1 and Tcf1 (Galceran et al, 2001). TCF-binding sites have been found in the mouse Brachyury promoter, and their mutation led to loss of Brachyury expression and Wnt responsiveness (Arnold et al, 2000;Yamaguchi et al, 1999b). However, cis-regulatory elements responsible for the notochord-specific expression of the mouse Brachyury have not been well characterized.…”
Section: Other Factors Controlling Ci-bra Transcriptionmentioning
confidence: 99%
“…The regulatory sequences required for the expression of Brachyury in the primitive streak are present within 500 bp upstream of the transcription start site of this gene (Clements et al, 1996;Yamaguchi et al, 1999a). A part of the Brachyury expression domain in the primitive streak depends on Wnt3a (Yamaguchi et al, 1999b) and the downstream effectors Lef1 and Tcf1 (Galceran et al, 2001). TCF-binding sites have been found in the mouse Brachyury promoter, and their mutation led to loss of Brachyury expression and Wnt responsiveness (Arnold et al, 2000;Yamaguchi et al, 1999b).…”
Section: Other Factors Controlling Ci-bra Transcriptionmentioning
confidence: 99%